A study to develop clinical decision rules for the emergency department use of radiography in acute ankle injuries. - Stiell, Ian Gilmour. (University of Ottawa (Canada), 1991)
This study was performed in two phases. The goal of Phase 0 was to determine the current use of radiography in ankle injury patients in two large university hospitals. The goal of Phase I was to develop clinical decision rules that are sensitive for detecting significant fractures in adult ankle injury patients. All 70 significant fractures found in the 689 ankle x-ray series performed were identified among people who had pain near the malleoli and who either: (1) were age 55 or greater, or (2) had localized bone tenderness of the posterior edge or tip of either malleolus, or (3) were unable to bear weight both immediately after the injury and in the emergency department. Combining these four predictors yielded a decision rule that was 100% sensitive and 40.1% specific for detecting ankle fractures, and would allow a reduction of 36.0% of ankle x-ray series ordered. This study confirmed that the majority of ankle injury patients are currently being referred for radiography but that the yield of the x-rays for fracture is relatively low. Decision rules may permit clinicians to confidently reduce the number of x-rays ordered in adult ankle injury patients and thereby reduce unnecessary costs to the health care system. (Abstract shortened by UMI.)
Keywords: Health Sciences, General.